Pengaruh Pengaplikasian Pupuk Organik Cair Limbah Kulit Pisang Kepok (Musa paradisiaca L.) Terhadap Pertumbuhan Microgreen Selada Merah (Lactuca sativa var. Crispa) - Chernovitha Azzahra Putri; Nurlaila Nurlaila; Tuti Heiriyani (Universitas Lambung Mangkurat, 2026)
This research aims to determine the effect of applying liquid organic fertilizer made from kepok banana peel waste (Musa paradisiaca L.) on the growth of red lettuce microgreens (Lactuca sativa var. Crispa). In the context of urban farming, which is becoming increasingly popular, microgreens are an attractive option because they can be harvested quickly and have high nutritional content. This study utilized a Completely Randomized Design (CRD) with variations in the concentration of liquid organic fertilizer to identify the optimal concentration that yields the best results for microgreen growth. The parameters measured included plant height, number of leaves, root length, and fresh weight per 100 seedlings. The results indicated that the use of liquid organic fertilizer from kepok banana peel waste significantly affected the growth of red lettuce microgreens. The optimal concentration found was 400 ml per liter of water, which produced the best growth in terms of plant height, number of leaves, root length, and fresh weight per 100 seedlings. The average plant height reached 5.73 cm, with an average of 3.45 leaves per plant, and a fresh weight per tray of 7.70 grams. This research is expected to provide useful information regarding the use of organic waste as fertilizer and its contribution to increasing the production of healthy vegetables. By utilizing kepok banana peel waste, this study has the potential not only to enhance agricultural yields but also to reduce waste management issues in the environment.